Long-term efficacy of hydrotherapy on balance function in patients with Parkinson’s disease: a systematic review and meta-analysis - Liu, Zicai; Huang, Miao; Liao, Ya; Xie, Xiuying; Zhu, Pingan; Liu, Yangyou; Tan, Cheng (Frontiers in Aging Neuroscience, 2023)
Background Hydrotherapy can improve the motor and non-motor symptoms of Parkinson’s disease (PD), but the long-term effects of hydrotherapy on PD are still unclear. Objective The purpose of this systematic evaluation and meta-analysis was to explore the long-term effects of hydrotherapy on balance function in PD patients. Methods A systematic search of five databases was conducted to identify appropriate randomized controlled trials (RCTs) according to the established inclusion and exclusion criteria. The general characteristics and outcome data (balance, exercise, mobility, quality of life, etc.) of the included studies were extracted, and the quality of the included studies was evaluated using the Cochrane risk of bias assessment tool. Finally, the outcome data were integrated for meta-analysis. Results A total of 149 articles were screened, and 5 high-quality RCTs involving 135 PD patients were included. The results of the meta-analysis showed positive long-term effects of hydrotherapy on balance function compared to the control group (SMD = 0.69; 95% CI = 0.21, 1.17; p = 0.005; I2 = 44%), However, there were no significant long-term effects of hydrotherapy on motor function (SMD = 0.06; 95% CI = −0.33, 0.44; p = 0.77; I2 = 0%), mobility and quality of life (SMD = −0.21; 95% CI = −0.98, 0.57; p = 0.6; I2 = 71%). Interestingly, the results of the sensitivity analysis performed on mobility showed a clear continuation effect of hydrotherapy on mobility compared to the control group (SMD = −0.80; 95% CI = −1.23, −0.37; p < 0.001; I2 = 0%). Conclusion The long-term effects of hydrotherapy on PD patients mainly focus on balance function, and the continuous effects on motor function, mobility, and quality of life are not obvious.